Henry Wilson and the era of Reconstruction - Myers, John L. (University Press of America, 2009)
Already a leader of the Republican party when the Civil War began, Henry Wilson had distinguished himself as the most important Congressional figure on military and antislavery and pro-black legislation during the war.